2007
DOI: 10.1029/2006jc003748
|View full text |Cite
|
Sign up to set email alerts
|

Physical mixing effects on iron biogeochemical cycling: FeCycle experiment

Abstract: [1] The effects of physical processes on the distribution, speciation, and sources/sinks for Fe in a high-nutrient low-chlorophyll (HNLC) region were assessed during FeCycle, a mesoscale SF 6 tracer release during February 2003 (austral summer) to the SE of New Zealand. Physical mixing processes were prevalent during FeCycle with rapid patch growth (strain rate g = 0.17-0.20 d À1 ) from a circular shape (50 km 2 ) into a long filament of $400 km 2 by day 10. Slippage between layers saw the patch-head overlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 88 publications
(149 reference statements)
5
36
0
Order By: Relevance
“…Hydrocarboxylic acids, such as glucaric acid, affect photoreduction of Fe(III) and may be released from phytoplankton (Kuma et al, 1992;Öztürk et al, 2004) while their direct effect on Fe(II) oxidation remains to be shown. However, organic Fe(II) complexation and consequential effects on the lifetime of Fe(II) in seawater have been suggested previously (Croot et al, 2001(Croot et al, , 2007Breitbarth et al, 2009). Our data suggest two possible mechanisms tying into Fe(II) cycling at different pH.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrocarboxylic acids, such as glucaric acid, affect photoreduction of Fe(III) and may be released from phytoplankton (Kuma et al, 1992;Öztürk et al, 2004) while their direct effect on Fe(II) oxidation remains to be shown. However, organic Fe(II) complexation and consequential effects on the lifetime of Fe(II) in seawater have been suggested previously (Croot et al, 2001(Croot et al, , 2007Breitbarth et al, 2009). Our data suggest two possible mechanisms tying into Fe(II) cycling at different pH.…”
Section: Resultsmentioning
confidence: 99%
“…This problem was minimized by using black Teflon tubing for all solutions (including the waste line), and by placing the detector and the pump in a dark case and covering them with a dark cloth. On a few cruises, several samples were followed to complete decay and repeatedly analyzed to better constrain the blank values and test for the presence of more slowly-oxidized Fe(II) species, as was recently reported by Croot et al (2007) in the southwest Pacific. The blank values were found to be stable and Fe(II) oxidation rates remained unchanged throughout.…”
Section: Fe(ii) Determinationmentioning
confidence: 99%
“…Consequently, a continuous supply of both energy and electrons is required to drive the redox cycle and maintain measurable Fe(II) concentrations. To date, Fe(II) concentrations ranging from a few picomolars to several nanomolars have been reported in a number of aquatic environments (Emmenegger et al, 2001;Shaked et al, 2002;Boyé et al, 2006;Croot et al, 2007;Hopkinson and Barbeau, 2007;Moffett et al, 2007;Ussher et al, 2007). In near surface waters, solar irradiance drives photochemical reduction of iron by direct photolysis and/or by indirect photolysis of chromophoric dissolved organic matter (CDOM) to form Fe(III)-reducing radicals (Barbeau, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the parameterizations on energy dissipation and turbulence in the OSBL are based on the assumption that MLD = XLD, which is often not the case in a dynamic ocean [ Brainerd and Gregg , ; Croot et al , ; Cisewski et al , ; Noh and Lee , ; Stevens et al , ; Sutherland et al , ; Franks , ]. Observations of differences between the MLD and the XLD have been commented on in early microstructure experiments [ Shay and Gregg , ; Dewey and Moum , ]; however, there have been relatively few studies that have investigated the nature of this difference as it requires specialized instruments to measure turbulent properties and large data sets to quantitatively compare the MLD and XLD.…”
Section: Introductionmentioning
confidence: 99%